Assessment of entrepreneurial innovation on sustainability of industrial leather clusters in Kano State - Yusuf, Hafsat; Danlami, Sulaiman; Ebikweluye, Loveth Esezobor (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
Purpose: Entrepreneurial innovation is a major contributor to the growth and sustainability of business enterprises, which in turn boosts the economy. It has also been acknowledged by scholars and professionals that entrepreneurial innovation is a driver of business survival and sustainability. Thus, the study examined the effect of entrepreneurial innovation on the sustainability of industrial leather clusters in Kofar Wambai, Kano State. Methodology: A cross-sectional survey design using primary data was adopted using a structured questionnaire. The unit of analysis is the artisans of industrial leather clusters in Kofar Wambai, Kano State. A simple random sampling technique was employed to select the sample size of eighty-six (86). To test the proposed hypothesis, the multiple regression analytical tool was employed. Results and conclusion: The result of the analysis revealed a positive and significant effect of the independent variable, entrepreneurial innovation (process and product innovativeness), on the sustainability of industrial leather clusters in Kofar Wambai, Kano State. Implication of findings: The study recommends artisans in Kofar Wambai adopt pursuing a concurrent, dual-focus innovation (process and product) strategy to maximize sustainability gain in Kofar Wambai industrial leather clusters of Kano state.